An Arabidopsis Secondary Metabolite Directly Targets Expression of the Bacterial Type III Secretion System to Inhibit Bacterial Virulence - Wang, Wei; Yang, Jing; Zhang, Jian; Liu, Yong-Xin; Tian, Caiping; Qu, Baoyuan; Gao, Chulei; Xin, Peiyong; Cheng, Shujing; Zhang, Wenjing; Miao, Pei; Li, Lei; et al. (Cell host & microbe, 2020)
Plants deploy a variety of secondary metabolites to fend off pathogen attack. Although defense compounds are generally considered toxic to microbes, the exact mechanisms are often unknown. Here, we show that the Arabidopsis defense compound sulforaphane (SFN) functions primarily by inhibiting Pseudomonas syringae type III secretion system (TTSS) genes, which are essential for pathogenesis. Plants lacking the aliphatic glucosinolate pathway, which do not accumulate SFN, were unable to attenuate TTSS gene expression and exhibited increased susceptibility to P. syringae strains that cannot detoxify SFN. Chemoproteomics analyses showed that SFN covalently modified the cysteine at position 209 of HrpS, a key transcription factor controlling TTSS gene expression. Site-directed mutagenesis and functional analyses further confirmed that Cys209 was responsible for bacterial sensitivity to SFN in vitro and sensitivity to plant defenses conferred by the aliphatic glucosinolate pathway. Collectively, these results illustrate a previously unknown mechanism by which plants disarm a pathogenic bacterium.